If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 9(x + 1) + 4(x + 1) = 6x + -6 Reorder the terms: 9(1 + x) + 4(x + 1) = 6x + -6 (1 * 9 + x * 9) + 4(x + 1) = 6x + -6 (9 + 9x) + 4(x + 1) = 6x + -6 Reorder the terms: 9 + 9x + 4(1 + x) = 6x + -6 9 + 9x + (1 * 4 + x * 4) = 6x + -6 9 + 9x + (4 + 4x) = 6x + -6 Reorder the terms: 9 + 4 + 9x + 4x = 6x + -6 Combine like terms: 9 + 4 = 13 13 + 9x + 4x = 6x + -6 Combine like terms: 9x + 4x = 13x 13 + 13x = 6x + -6 Reorder the terms: 13 + 13x = -6 + 6x Solving 13 + 13x = -6 + 6x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-6x' to each side of the equation. 13 + 13x + -6x = -6 + 6x + -6x Combine like terms: 13x + -6x = 7x 13 + 7x = -6 + 6x + -6x Combine like terms: 6x + -6x = 0 13 + 7x = -6 + 0 13 + 7x = -6 Add '-13' to each side of the equation. 13 + -13 + 7x = -6 + -13 Combine like terms: 13 + -13 = 0 0 + 7x = -6 + -13 7x = -6 + -13 Combine like terms: -6 + -13 = -19 7x = -19 Divide each side by '7'. x = -2.714285714 Simplifying x = -2.714285714
| -6+11=-5-2 | | x^7-6x^5+2x^4-5=0 | | 2p-3=11 | | 3+7n=1+6n | | ln^3x=5 | | 5k^2=6-k | | (x+1)+(y-2)=7 | | 4x+25=8x+37 | | 16-2w=5w+9 | | 8x=215-13x | | 65+7x+5x-5=180 | | 5x^3+2x^2-x=0 | | 4y=12x-5 | | 7p+14=p-4 | | 6n^2-8=-93 | | -132=-7d-4d | | 8+3e^3x=26 | | 25a^2+8=108 | | 3h+12h=18 | | -5+3m=2m+2 | | X/7=10/2 | | 70+x+80+x+40=180 | | 8+3e=26 | | n^2=6+n | | 0=-4u^2-31u-50 | | X(5-x)=8-(x+3) | | 7-3x=-12 | | 3k+12k=60 | | 21v^2+71v+40=0 | | 3z-1=23-32 | | x^2-14x+51=6 | | X^3/x^5 |